Management Bandwidth LAN Menggunakan Ros&Pi Hole Sebagai Filterrilan SMK Mandiri 02 Balaraja - Anita Restuintin; Po Abas Sunarya; Abdul Mukarobi Qodratullah (UNIVERSITAS RAHARJA, 2021)
Science and technology have changed the way Indonesians view activities. Information technology in the education system, but these developments are not yet equivalent to human resources that determine success in Indonesia in general. The Internet is a tool that is interconnected through communication media and transmission media. The Internet is included in the computer network section, where the computer network consists of Local Area Network (LAN), Wide Area Network (MAN) and Metropolitan Area Network (MAN). Of these three types of networks, computer networks are often used for an educational institutionand other general diamonds are LAN networks, because LAN networks are local networks that cover only one area or one building. The research method is divided into two stages, the first stage is data collection by means of observation, interviews and literature study, the second stage is the design using the forward chaining approach, which is a method that collects facts first and then can produce solutions/conclusions. While the design of the system built using Raspberry Pi which has sockets for keyboard and mouse.